Primary endobronchial amyloidosis: A rare case of endobronchial tumor. (2018) - Lal, Amos; Akhtar, Jamal; Khan, Mohammad Saud; Chen, Yayan; Yaron Goldman,
Abstract: Primary localized endobronchial amyloidosis is a rare entity, as pulmonary amyloidosis most commonly occurs as a part of systemic AL amyloidosis. It can be asymptomatic or can present with nonspecific symptoms such as progressive dyspnea, cough, wheezing and rarely respiratory failure. It is frequently misdiagnosed as asthma, COPD or pneumonia. Solitary endobronchial amyloidosis having a nodular appearance can mimic endobronchial tumor. The diagnosis is usually delayed by 8–37 months. The average life expectancy for primary tracheobronchial amyloidosis is approximately 9 years, so the early diagnosis of this disease is very critical to improve the prognosis of patients. We are presenting a case of 65 year old male which was initially diagnosed and treated as asthma exacerbation with minimal improvement. Further workup was done with CT chest, bronchoscopy and biopsy because of persistent shortness of breath, which revealed primary localized solitary endobronchial amyloidosis.